Achieving High Thermal Conductivity in Epoxy Resin Composites by Synergistically Utilizing Al2O3 Framework and BN Sheet as Fillers. Issue 11 (5th August 2022) - Wang, Xubin; Zhang, Changhai; Zhang, Tiandong; Li, Zhonghua; Tang, Chao; Chi, Qingguo
Abstract: The application of high thermal conductive Epoxy resin (EP) is an efficient way to improve the heat dissipation in electronic device. In this work, the thermal conductivity of EP is significantly improved by synergistically utilizing Al2 O3 framework (AF) and boron nitride sheet (BN) as fillers. The polyurethane foams with different pore sizes are used to prepare AF for the first time. The microstructure characterization demonstrates the successful preparation of AF/EP and AF‐BN/EP with different AF pore size. The thermal conductivity of AF/EP is superior to that of Al2 O3 /EP composites with randomly distributed Al2 O3 nanoparticles. The smaller pore of AF is beneficial to achieving a greater thermal conductivity in AF/EP composites. Especially, by combing BN with AF can further improve the thermal conductivity of AF‐BN/EP composites. The optimal value of 1.18 W m −1 K −1 (5.42 times high than pure EP) is obtained for 60 ppi‐AF‐20 wt% BN/EP composite. Besides, the dielectric property shows that by combining of AF and BN increases the permittivity, as well as low dielectric loss. The high thermal conductivity and excellent dielectric property are simultaneously achieved by synergistically utilizing AF and BN fillers, the resultant EP composites have great potential to be used in electronic devices. Abstract : The Al2 O3 framework‐boron nitride/epoxy resin (AF‐BN/EP) composites are obtained by vacuum impregnation of different contents of BN/EP on different pore size of AF. Finally, the 60 ppi‐AF‐20 wt% BN/EP composites obtain a thermal conductivity of 1.18 W m −1 K −1, a thermal conductivity enhancement of 542%, and excellent dielectric properties.